Omega-3 LC-PUFA consumption is now recommended for women of childbearing age and during pregnancy to protect against preterm and early preterm birth: implementing this recommendation in a sustainable manner - Baker, Ella J.; Calder, Philip C.; Kermack, Alex J.; Brown, Jonathan E.; Mustapha, Moriam; Kitson-Reynolds, Ellen; Garvey, Josephine J. (Frontiers in Nutrition, 2024)
Preterm birth (delivery prior to 37 weeks) appears to be rising globally, increasing the risk of a myriad of down-stream disorders which affect families, their offspring and society, including increased morbidity, mortality and economic costs. Strategies for prevention of preterm birth have therefore become a priority amongst healthcare providers. One proposed strategy is increased consumption of Omega-3 long-chain polyunsaturated fatty acids (LC-PUFAs), particularly docosahexaenoic acid (DHA) (from food or supplements) in women of childbearing age and during pregnancy. It is hypothesised that Omega-3 LC-PUFAs, through several different actions, reduce the risk of early onset labor or lengthen gestation. An expert group, acting on behalf of several relevant organisations, recently published guidance based on compelling trial evidence for increased Omega-3 LC-PUFA intake to protect women of childbearing age and during pregnancy from preterm birth (PTB) and early preterm birth (ePTB). Here, we consider how this guidance can be achieved in a sustainable manner. We present data on suitable, efficacious alternatives to fish as a source of Omega-3 LC-PUFAs, so that while aiming to protect families and society against PTB and ePTB there is no increased burden on other species on our vulnerable planet. Finally, how the guidance can be implemented in practice is discussed, with consideration for those most at risk and effective ways of communicating this important message.